Comparative Efficacy and Safety of the Non–Vitamin K Antagonist Oral Anticoagulants for Patients with Nonvalvular Atrial Fibrillation - Senoo, Keitaro; Lip, Gregory Y. H. (Seminars in Thrombosis and Hemostasis, 2015)
The non–vitamin K antagonist oral anticoagulants (NOACs), such as the thrombin inhibitor (dabigatran) and the direct factor Xa inhibitors (rivaroxaban, apixaban, and edoxaban), have been shown to be at least as efficacious and safe as conventional oral anticoagulants, such as the vitamin K antagonists (VKAs) (e.g., warfarin), for stroke prevention in patients with nonvalvular atrial fibrillation (NVAF). Each NOAC has various advantages and specific features, and therefore decisions regarding appropriate stroke prevention require individual assessment of stroke and bleeding risk on anticoagulation with VKA therapy and NOACs when starting on any of these drugs. This review briefly describes the results of the four NOACs clinical randomized trials and discusses how they might impact clinical practice and choice of anticoagulants in atrial fibrillation patients. Moreover, this review discusses the differences of the proposed management of antithrombotic therapy in several international guidelines and pragmatic issues of NOACs for stroke prophylaxis.
Keywords: non-VKA oral anticoagulants; vitamin K antagonist; atrial fibrillation; stroke prevention; clinical trial